A Question of Costliness: Time Horizons and Interstate Signaling. (September 2019) - Haynes, Kyle
This article examines how interstate signaling processes operate under multiple dimensions of uncertainty. The existing signaling literature largely assumes that states communicate and infer one another's intentions in a simplified context where they are only uncertain about one component of the other's preferences. Relaxing this unrealistic assumption, I develop a model of interstate reassurance in which the receiver is uncertain of both the compatibility of the sender's goals and its time horizons. If a receiving state is unsure of the sending state's time horizons, it is more difficult to determine the costliness of a given signal, and thus how credible it is as an indicator of the sender's preferences. I show that under certain conditions, shorter time horizons lead to more credible signaling as states become less willing to incur the short-term costs of misrepresentation. Under other conditions, however, shortened time horizons can incentivize hedging behavior, thus undermining a benign state's ability to credibly signal its intentions. Finally, the model reveals that multidimensional uncertainty can actually facilitate cooperation across a wider range of conditions than one-dimensional uncertainty. I present two brief case illustrations and discuss the model's implications for contemporary US–China relations.